Source Rock Characterization of the Eocene-Miocene, Central Deep, North East Java Basin - Fauzan Iqbal Hidayat; Ade Yogi; Eriko Sabra; Taufik Ramli; Muhammad Firdaus; Hanif Mersil Saleh; Gadis Ghia Arviallyn; Andi Setyo Wibowo (Jurnal Geologi dan Sumberdaya Mineral, 2022)
This study was conducted to obtain the characteristics of the source rock through organic geochemical analysis in Central Deep, NE Java Basin, in the field off the north coast of Madura. Three samples of Cassiopeia-1, Pollen-1, and Alpha-1 wells were analyzed using organic geochemical methods including Total Organic Carbon analysis, Maturity using vitrinite reflectance, Tmax, and Production Index data, and then analysis of the kerogen type, isoprenoid, sterane, and carbon isotope. Based on those data, an analysis was carried out to determine the origin of the material and the depositional environment. The rock samples in the three wells showed characteristics in TOC, maturity, kerogen type and source of organic material have a similarity. The source rock characteristics have a medium to a good category as source rock and tend to generate gas and a little oil from kerogen types II and III. This source rock is included in the category of immature to mature, deposited in delta until terrestrial depositional environment and contains sources terrestrial and marine organic material.Keywords: Madura, North East Java Basin, organic geochemical, source rock.